Increased Dosage of RAB39B Affects Neuronal Development and Could Explain the Cognitive Impairment in Male Patients with Distal Xq28 Copy Number Gains. Issue 3 (13th January 2014) - Vanmarsenille, Lieselot; Giannandrea, Maila; Fieremans, Nathalie; Verbeeck, Jelle; Belet, Stefanie; Raynaud, Martine; Vogels, Annick; Männik, Katrin; Õunap, Katrin; Jacqueline, Vigneron; Briault, Sylvain; Van, Hilde; et al.
<x xml:space="preserve">Abstract</x> In this study, we identified the same duplication of 500 kb on the X chromosome in unrelated male patients with intellectual disability. From the different genes included, the RAB39B gene was our prime candidate because loss‐of‐function had been described in relation to this condition. Indeed, overexpression of this gene in primary neuronal cells resulted in a decrease of neuronal branching and presynaptic terminals, providing evidence that an increased dosage of RAB39B in humans can affect neuronal development and function. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>